MODAL SOSIAL DALAM MITIGASI STRUKTURAL BANJIR: STUDI KASUS FORUM PENGURANGAN RISIKO BENCANA DI DAS KALIJOMPO - Gymnastiar Tira Wicaksana; Joko Mulyono; Jati Arifiyanti (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
Disasters are events that endanger and disrupt community life. Mitigation is an effort to reduce disaster risk through structural and non-structural approaches. Jember Regency, East Java, has a fairly high potential for flood disasters, especially in the Kalijompo watershed area. The Kalijompo Disaster Risk Reduction Forum (F-PRB Kapo) is a disaster-aware community that plays a role in flood management in the region. The multidimensional characteristics of flood disasters encompassing infrastructure, policy, and natural resource management require a collaborative approach from various stakeholders. The research entitled "Social Capital in Structural Flood Mitigation: A Case Study of the Disaster Risk Reduction Forum in the Kalijompo Watershed" aims to identify, describe, and analyze the social capital of F-PRB Kapo in structural flood disaster mitigation programs. The research method uses a qualitative approach with case studies, purposive informant selection, and data collection through observation, interviews, and documentation. Data validity is ensured through triangulation, while data analysis is conducted through reduction, presentation, and verification. Using Robert D. Putnam's social capital theory with the concepts of trust, social norms, and social networks, this research found that social capital is very important in disaster mitigation by F-PRB Kapo. The continuity of these three elements creates an integrated system that transforms social relationships into effective physical disaster prevention infrastructure